The profile of the adolescent worker within the scope of professional learning - Castro, Antonia Ozana Silva Luna de; Peruzzo, Juliane Feix (Argumentum, 2024)
The article discusses the work culture underlying the Apprenticeship Programme, one of the main strategies for combating child labour. This debate is based on bibliographic research, particularly through analysis of the curricular guidelines for Professional and Technological Education (EPT) and Apprenticeships. It sets out the trends in the form of the labour market and the configuration of labour activities for working adolescents through analysis of the learning guidelines of the SNA and CNI and, through data taken from the IBGE, CAGED, and RAIS databases, it presents the main occupations that took on apprentices from 2019 to 2022. We observe that the resulting worker profile has an entrepreneurial nature, that has been adapted and shaped for a flexible market riven with informality, unemployment, and insecurity.